Size and shape effects in β-NaGdF4: Yb3+, Er3+ nanocrystals. (3rd April 2017) - Noculak, Agnieszka; Podhorodecki, Artur
Abstract: Three sets of  β -NaGdF4 :Yb 3+, Er 3+ nanocrystals (NCs) with different shapes (spherical and more complex flower shapes), different sizes (6–17 nm) and Yb 3+ concentrations (2%–15%) were synthesized by a co-precipitation method using oleic acid as a stabilizing agent. The uncommon, single-crystalline flower-shaped NCs were obtained by simply adjusting the fluorine-to-lanthanides molar ratio. Additionally, some of the NCs with different sizes have been covered by the un-doped shell. The crystal phase, shapes and sizes of all NCs were examined using transmission electron microscopy and x-ray diffraction methods. Simultaneously, upconversion luminescence and lifetimes, under 980 nm excitation, were measured and the changes in green to red (G/R) emission ratios as well as emission decay times were correlated with the evolution of nanocrystal sizes and surface to volume ratios. Three different mechanisms responsible for the changes in G/R ratios were presented and discussed.